UPAYA PENGEMBANGAN PELAYANAN KESEHATAN TERHADAP MASYARAKAT MELALUI APLIKASI MOBILE JKN - Anisa Zaqia; Sabila, Anindya; Azhari, Fanny Aulia (Universitas Cenderawasih, 2024)
Technology has brought major changes in government, including the public health sector, with the implementation of e-government such as the development of Information Systems on the National Health Insurance (JKN). BPJS Kesehatan through the JKN Mobile Application presents innovative digital health administration services to facilitate public access to JKN information and services. The purpose of this study was to analyze efforts to develop health services to the community through the JKN Mobile Application. The research method used is a literature review, with a multimodal approach combining literature analysis of relevant theories and documents with virtual interviews to obtain empirical data from informants through digital platforms. This combination allows for a holistic understanding, with the literature study as a theoretical basis and the interviews as a source of current perspectives, which are then analyzed in triangulation for data validity. The results showed that the benefits of using the JKN Mobile Application can facilitate the community in accessing information related to BPJS Health such as information about registration, hospital referrals, and facilitate digital-based transactions. In addition to the benefits, there are challenges faced by the community, namely, limited internet access constraints, and low public understanding of the use of the JKN Mobile Application.